Media Consumption Influence on Enhancing Public Participation Influenced by Perception and Solidarity Values in Timor-Leste - Miguel Gonçalves; Sunarto; Nurul Hasfi (Jurnal Komunikasi, 2024)
This study has aim to determine the effect of political consumption in mass media on increasing public participation in Timor-Leste, which is influenced by perceptions and solidarity values. To answer this research questions we applied the Uses and Gratification theory and conducted a survey of 68 people from Comoro Village, Dom Aleixo Administrative Post, Dili, Timor-Leste. This study found that H1 with a sig value of 0.004 <0.05 or t count with a value of 2.959> t table with a value of 0.235, then Ha is accepted and Ho is rejected. So there is an influence between variable (X) and variable (A1) on variable (Y). H2 with a sig value of 0.008> 0.05 or t count with a value of 1.773> t table with a value of 3.846, then Ha is accepted and Ho is rejected. There is an influence between variables (X), (A2) on (Y). The results of H3 obtained a sign value of 0.041> 0.05 or t count with a value of 2.083> t table with a value of 0.235, then Ha is accepted and Ho is rejected. There is an influence between variables X, A1 and A2 on variable Y. The results show that theoretically community participation is influenced by other factors, namely media use, political issues and solidarity values. Practically, media content as a way and its delivery in the action of how to participate in society. Thus, this research shows that political content in the media has a major influence on the level of public participation and solidarity of the vulnerable group, so it needs to continue to be developed in Timor-Leste society.